2018
DOI: 10.1136/jech-2017-210403
|View full text |Cite
|
Sign up to set email alerts
|

Association between birth weight and educational attainment: an individual-based pooled analysis of nine twin cohorts

Abstract: Although associations are weak and somewhat inconsistent, our results suggest that intrauterine environment may play a role when explaining the association between birth weight and educational attainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Using the twin design, we demonstrated that intrauterine conditions affecting smaller birth size are associated with shorter height and lower BMI from early childhood to adulthood (Jelenkovic et al, 2017;, which are consistent with prior studies. On the other hand, our findings that birth weight was only weakly associated with adult education in discordant twin pairs (Jelenkovic, Mikkonen et al, 2018) and that males and females having opposite-sex co-twins showed no consistent differences as compared to those having same-sex co-twins in height and BMI (Bogl et al, 2017) are not consistent with previous hypotheses. Because there is a well-known tendency to publish positive results (Thornton & Lee, 2000), these types of large collaborative studies are important to validly test hypotheses and estimate effect sizes not inflated by publication bias.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Using the twin design, we demonstrated that intrauterine conditions affecting smaller birth size are associated with shorter height and lower BMI from early childhood to adulthood (Jelenkovic et al, 2017;, which are consistent with prior studies. On the other hand, our findings that birth weight was only weakly associated with adult education in discordant twin pairs (Jelenkovic, Mikkonen et al, 2018) and that males and females having opposite-sex co-twins showed no consistent differences as compared to those having same-sex co-twins in height and BMI (Bogl et al, 2017) are not consistent with previous hypotheses. Because there is a well-known tendency to publish positive results (Thornton & Lee, 2000), these types of large collaborative studies are important to validly test hypotheses and estimate effect sizes not inflated by publication bias.…”
Section: Discussioncontrasting
confidence: 91%
“…We used the discordant twin pair design to analyze how differences in birth weight between co-twins, which may reflect differences in the intrauterine environment, can affect differences in education in adulthood. We found that the lighter co-twin at birth had shorter education than the heavier co-twin, but the differences were very small and somewhat inconsistent between birth cohorts and zygosities (Jelenkovic, Mikkonen et al, 2018). In another study, we analyzed how parental education modifies the genetic and environmental variation of BMI from infancy to old age in the cultural-geographic regions (Silventoinen et al, 2019).…”
Section: Major Findings From Studies On Education and Smokingmentioning
confidence: 98%
“…Considering that Full-Scale IQ is less frequently included in large population studies due to its heavy burden on examiners and participants, we aimed to maximize use of these data as others have before us. 57 59 In CANDLE, full-scale IQ was derived from the 10 subtests in the SB-5 addressing five cognitive factors with verbal and nonverbal tests for each factor: knowledge, fluid reasoning, quantitative reasoning, visual-spatial processing, and working memory. In TIDES, Full-Scale IQ was estimated using the Tellegen and Briggs formula, 60 incorporating five WISC-V domains—verbal comprehension, visual spatial, fluid reasoning, working memory, and processing speed.…”
Section: Methodsmentioning
confidence: 99%
“…Low birth weight (a global index of poor fetal development) has been associated with a range of mental health problems (including attention-deficit hyperactivity disorder (ADHD), autism, bipolar disorder, depression, schizophrenia and suicide), [1][2][3][4][5][6][7][8] as well lower intelligence and socioeconomic status [9][10][11] (see also the Introduction in the supplementary material available at https://doi.org/10.1192/bjp.2021.15). These findings are consistent with the developmental origins of health and disease (DOHaD) hypothesis, 12,13 which states that adverse in utero and perinatal experiences may have long-lasting effects on adult health.…”
Section: Resultsmentioning
confidence: 99%